Limited predictive power of hospitalization variables for long‐term cognitive prognosis in adult patients with severe traumatic brain injury. Issue 1 (20th November 2012) - de, Maria Emília Rodrigues; Cavallazzi, Gisele; Formolo, Douglas Afonso; de, Lucas D'Ávila; Schmoeller, Roseli; Guarnieri, Ricardo; Schwarzbold, Marcelo Liborio; Diaz, Alexandre Paim; Hohl, Alexandre; Prediger, Rui D. S.; Mader, Maria Joana; Linhares, Marcelo Neves; et al.
<x xml:space="preserve">Abstract</x> Objectives Traumatic brain injury (TBI) is a main cause of mortality and morbidity. Association studies between hospitalization variables and cognitive impairment after TBI are frequently retrospective, including non‐consecutive patients showing variable degrees of TBI severity, and poor management of missing (drop out) cases. Methods We assessed prospectively the demographic and hospitalization variables of 234 consecutive patients with severe TBI (admission Glasgow Coma Scale [GCS] ≤8) and determined their independent association with cognitive performance in a representative sample (n = 46) of surviving patients (n = 172) evaluated 3 (±1.8) years after hospitalization. Results In all, 85% of patients were male and the mean age was 34 (SD ±13) years. The education level was 9 (±4.7) years. As expected, education and age showed a moderately to strong linear relationship with the cognitive performance in 14 of 15 neuropsychological tests (R coefficient = 0.6–0.8). The cognitive test scores were not independently associated with gender, admission GCS, associated trauma, and Marshal CT classification. Admission‐elevated blood glucose levels and the presence of sub‐arachnoid haemorrhage were independently associated with lower scores on Rey Auditory Verbal Learning retention and Logical Memory‐I tests, respectively. Conclusions After correction for education and age distribution, the variables that are commonly associated with mortality or Glasgow Outcome Scale including admission pupils' examination, Marshal CT Classification, GCS, and serum glucose showed a limited predictive power for long‐term cognitive prognosis. Identification of clinical, radiological, and laboratory variables as well as new biomarkers independently associated with cognitive outcome remains an important challenge for further work involving severe TBI patients.